Executive functions in mono- and bilingual children with language impairment – issues for speech-language pathology - Sandgren, Olof; Holmström, Ketty (Frontiers in Psychology, 2015)
The clinical assessment of language impairment (LI) in bilingual children imposes challenges for speech-language pathology services. Assessment tools standardized for monolingual populations increase the risk of misinterpreting bilingualism as language impairment. This Perspective article summarizes recent studies on the assessment of bilingual LI and presents new results on including nonlinguistic measures of executive functions in the diagnostic assessment. Executive functions shows clinical utility as less subjected to language use and exposure than linguistic measures. A possible bilingual advantage, and consequences for speech-language pathology practices and future research are discussed.